(untitled) (MAUSAM, 1963)
The realisation that the earth as a whole is experiencing a minor climatic fluctuation coupled with the fact that the precise modern science of climatology provides objective means of indicating the extent and intensity of such changes, has in the recent years given considerable impetus to the study of climatic changes.